De Delos a Atenas: el viaje del tesoro (Iter, 2022)
This paper considers the symbolic value of the transfer of the treasure from Delosto Athens to plot around a series of historical events of the s. V BC related to dramaticchanges in the sphere of power, society and the economy. These three elements are,in turn, examined and tested through philology, etymology, and semantics. Becausethese words have the fundamental role of guiding and synthesizing the story that weintend to make manifest here. From this account, we believe, an explanation of thecirculation of money and wealth emerges more clearly. Taxes, therefore, appear inthis plot that is woven between power, society and the economy.
Keywords: society - power - taxes - riches - leitougía